2009
DOI: 10.1016/j.dnarep.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Distinct kinetics of human DNA ligases I, IIIα, IIIβ, and IV reveal direct DNA sensing ability and differential physiological functions in DNA repair

Abstract: The three human LIG genes encode polypeptides that catalyze phosphodiester bond formation during DNA replication, recombination and repair. While numerous studies have identified protein partners of the human DNA ligases (hLigs), there has been little characterization of the catalytic properties of these enzymes. In this study, we developed and optimized a fluorescence-based DNA ligation assay to characterize the activities of purified hLigs. Although hLigI joins DNA nicks, it has no detectable activity on lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…An unusual feature of purified DNA ligase IV family proteins is that they appear to catalyze only a single ligation event because of inefficient readenylation following ligation (32,42,45). Recently, it has been shown that XLF promotes readenylation of DNA ligase IV-XRCC4, and it was suggested that this readenylation may enable DNA ligase IV-XRCC4 to join both strands at a ligatable DSB (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An unusual feature of purified DNA ligase IV family proteins is that they appear to catalyze only a single ligation event because of inefficient readenylation following ligation (32,42,45). Recently, it has been shown that XLF promotes readenylation of DNA ligase IV-XRCC4, and it was suggested that this readenylation may enable DNA ligase IV-XRCC4 to join both strands at a ligatable DSB (32).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA ligase IV family is distinct from the other families of eukaryotic DNA ligases in that the purified enzyme is not only predominantly preadenylated but also appears to be capable of completing only a single ligation reaction (32,(42)(43)(44)(45). Because XLF stimulates DNA joining by DNA ligase IV-XRCC4 (31-34, 46), we asked whether Nej1 modulates the catalytic activity of Dnl4-Lif1.…”
Section: Nej1 Stimulates Dna Joining By Dnl4-lif1 By Atp-independent mentioning
confidence: 99%
“…An already adenylated ligase cannot engage this substrate; this would occur if the “spent” ligase’s active site is re-adenylated in situ , or if the spent ligase is exchanged for another, already adenylated ligase. The former problem might be mitigated somewhat by the general resistance of ligase IV to re-adenylation, relative to other mammalian ligases [127]. Possibly more significantly, aprataxin can remove the adenylate on the substrate regardless of the reason why the ligase is also adenylated; the NHEJ complex is thus reset for another ligation attempt [61, 62].…”
Section: Strategies For Resolving Endsmentioning
confidence: 99%
“…Purified LigI fractions were pooled, concentrated using a 50 kDa MWCO centrifugal filter (EMD Millipore), and then stored at −80°C. LigIIIβ and the LigIV/XRCC4 complex were purified from E. coli and insect cells, respectively as described previously (53,54). …”
Section: Methodsmentioning
confidence: 99%
“…Nick joining was measured using radioactive- and fluorescence-based assays (53,54). The concentrations of oligonucleotides (Integrated DNA Technologies) DNA were measured using absorbance at 260 nm.…”
Section: Methodsmentioning
confidence: 99%